Epigenetic modulation by small molecule compounds for neurodegenerative disorders. (June 2018) - Singh, Akash Kumar; Halder-Sinha, Sarmistha; Clement, James P.; Kundu, Tapas K.
Graphical abstract: Abstract: The accumulation of somatic and genetic mutations which altered the structure and coding information of the DNA are the major cause of neurological disorders. However, our recent understanding of molecular mechanisms of 'epigenetic' phenomenon reveals that the modifications of chromatin play a significant role in the development and severity of neurological disorders. These epigenetic processes are dynamic and reversible as compared to genetic ablations which are stable and irreversible. Therefore, targeting these epigenetic processes through small molecule modulators are of great therapeutic potential. To date, large number of small molecule modulators have been discovered which are capable of altering the brain pathology by targeting epigenetic enzymes. In this review, we shall put forward the key studies supporting the role of altered epigenetic processes in neurological disorders with especial emphasis on neurodegenerative disorders. A few small molecule modulators which have been shown to possess promising results in the animal model system of neurological disorders will also be discussed with future perspectives.